Jesuit Art Brill's Research Perspectives in Jesuit Studies - Mochizuki, Mia M. (Brill Research Perspectives in Humanities and Social Sciences, 2022)
Mia Mochizuki draws upon masterpieces and material culture from around the world to show how the pre-suppression Society of Jesus (1540-1773) pioneered structural innovations in the history of the image. ; Readership: All interested in early modern, religious, and global art history, and anyone concerned with Renaissance and Baroque art and architecture, Jesuit studies, and the world-wide circulation of prints. Keywords: Renaissance art, Baroque art, religious art, Jesuit art and architecture, global art history, print history, 1540-1773, Jesuit style, Spiritual Exercises, Evangelicae historiae imagines, Imago primi saeculi Societatis Iesu, Ignatius of Loyola, Francis Xavier.